BREACH OF PERFORMANCE IN PHOTOGRAPHY SERVICES: THE CLIENT DOES NOT PAY THE FEES AGREED IN THE CONTRACT BASED ON THE CIVIL CODE AND LAW NO. 8 OF 1999 CONCERNING CONSUMER PROTECTION - Syafrizal Syafrizal; Azmiati Zuliah; Andi Maysarah (NOMOI Law Review, 2026)
This article examines the legal consequences of non-payment in photography service agreements in accordance with the Indonesian Civil Code (KUHPerdata) and the Consumer Protection Law (UU No. 8/1999). The objective of this study is to examine different legislative frameworks that safeguard photographers against client non-payment and to evaluate the effectiveness of legal remedies in resolving these disputes. The research employed a qualitative methodology, collecting data through semi-structured interviews with attorneys, photographers, and clients, in addition to analyzing documents such as contracts, judicial decisions, and relevant statutes. The discussion pertains to the concept of